DEVELOPMENT OF A BISCUIT FROM BEER RESIDUES - Gaio, Josimar; da Silveira, Stella Moura; de Proencio, Gabriela; de Souza, Edson Luiz; Soares, Fabiana Andreia Schäfer De Martini (Anuário Pesquisa e Extensão Unoesc Videira, 2017)
In the beer-making process, is the disposal of raw material used for the preparation of beer wort, known as bagasse malt or beer bagasse. The presence of fiber, protein residue and sugars, makes this bagasse with potential for use in products developed in baking, such as loaves of bread and biscuits, where the increase, especially in fiber, beneficial to the consumer from a nutritional point of view and functionality, reinforce the need to explore their technological potential in order to provide the consumer differentiated products, competitive market and special features enhancing health. To explore the possibility of using a residue rich in fiber, malt bagasse it, this study aimed to assess the technological potential of the use of malt bagasse as food, as well as the effects of the merger on the sensory and functional qualities the biscuit. For the manufacture of biscuits type cookie, first elaborated the malt bagasse flour. Cookies were designed to replacing wheat flour for malt bagasse flour. We were evaluated physicochemical composition (moisture, ash, proteins, carbohydrates, lipids and crude fiber), pH, acidity and activity of water. The sensory evaluation was performed with 30 panelists who evaluated the products in relation to appearance, flavor, odor, texture, using a hedonic scale of nine points. The potential consumers in the sensory analysis showed buying interest in the product. With the results obtained from the cookie and sensory analysis, expected recovery of the waste, increasing its value and bringing benefits to breweries industries and bakery.